Pengaruh Penambahan Abu Ampas Tebu Terhadap Sifat Mekanik Beton Pada Campuran Beton Normal - Akbar, Ilham; Djauhari, Zulfikar; Suryanita, Reni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The increasing in the population has an impact on the increasing of housing or bulding demand. The alternative solution to reduce the use of cement is by leveraging on natural materials such as baggase ash as a substitution part of cement in the concrete mixtures. Results from test showed that silicte (SiO2) content in bagasse ash was dominant, so that it might be used as a cement substitution to enhance the properties of the concrete. The specimens were tested at 7, 14, 28 and 56 days of treatment to observe the development of bagasse ash concrete with the variation of the ash at 5 % and 10 % from the weight of the cement. The result showed that the higher percentage of bagasse ash would result lower workability. The compressive strength has also decreased from normal concrete at 28 days of the treatment, at 5 % variaton that has a compressive strength at 21,221 MPa and 10% variation has a result at 16.411 MPa. Propertional to compressive test, the flexural test has also decreased from normal concrete, at 5% variation has a flexural strength at 3.60 MPa and at 10 % variation has a result at 3.40 MPa. It was because imperfect of bond between Ca(OH)2 with SiO2. Hence, instead of cement substitute, bagasse ash rolled better as filler in concrete mixtures. Keywords: bagasse ash, concrete, compressive strength, flexural strength, workability